Choroid plexus enlargement correlates with subcortical tau deposition in progressive supranuclear palsy - Na Wang; JiaYing Lu; XueLing Liu; JianPeng Liu; YuCheng Lu; ChengLing Xu; SiRong Piao; LiQin Yang; FengTao Liu; YuXin Li (Fluids and Barriers of the CNS)
Abstract Objective The choroid plexus (CP) has gained renewed attention for its role in waste clearance in neurodegenerative disorders. However, its involvement in progressive supranuclear palsy (PSP) remains unclear. This study aimed to investigate CP volume changes in patients with PSP compared to Parkinson’s disease (PD), and explore its relationship with tau deposition in PSP patients. Methods A total of 204 participants (92 PSP, 78 PD, 34 healthy controls (HC)) underwent structural MRI, with 63 PSP patients receiving 18F-Florzolotau positron emission tomography. CP volume was compared across the three groups, and its ability to differentiate PSP from PD was assessed. Mean standardized uptake value ratios (SUVRs) from bilateral subcortical regions were extracted: ROIs1 including early involved nuclei of red nucleus, subthalamic nucleus, raphe nuclei, and globus pallidus; ROIs2 including late involved nuclei of substantia nigra, locus coeruleus, putamen, and thalamus. The relationship between CP volume, tau deposition and clinical assessments was analyzed. Results PSP patients exhibited increased CP volume compared to PD and HC groups. The area under the curve value was 0.84 in differentiating PSP from PD, with CP volume and age as predictive variables. In the PSP group, CP volume was positively correlated with mean 18F-Florzolotau SUVRs in the ROIs2. Furthermore, in the PSP and PD groups, CP volume was negatively correlated with cognitive scores, but positively correlated with motor scores. Conclusions CP enlargement is a distinguishing feature of PSP and may serve as an imaging biomarker for tau accumulation, offering potential for differentiating PSP from PD.